2015
DOI: 10.1002/adfm.201500669
|View full text |Cite
|
Sign up to set email alerts
|

Plasmonic‐Induced Photon Recycling in Metal Halide Perovskite Solar Cells

Abstract: Organic–inorganic metal halide perovskite solar cells have emerged in the past few years to promise highly efficient photovoltaic devices at low costs. Here, temperature-sensitive core–shell Ag@TiO2 nanoparticles are successfully incorporated into perovskite solar cells through a low-temperature processing route, boosting the measured device efficiencies up to 16.3%. Experimental evidence is shown and a theoretical model is developed which predicts that the presence of highly polarizable nanoparticles enhances… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

8
191
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 209 publications
(203 citation statements)
references
References 74 publications
8
191
1
Order By: Relevance
“…photons are recycled) with the help of metal NPs [121,122]. According to the authors, it is the plasmonic-induced photon recycling by Ag@TiO 2 that improved the average PCE from 11.4%±1.3% to 13.7±1.2% ( Figure 23B) [120].…”
Section: Perovskite Solar Cells (Pscs)mentioning
confidence: 94%
See 4 more Smart Citations
“…photons are recycled) with the help of metal NPs [121,122]. According to the authors, it is the plasmonic-induced photon recycling by Ag@TiO 2 that improved the average PCE from 11.4%±1.3% to 13.7±1.2% ( Figure 23B) [120].…”
Section: Perovskite Solar Cells (Pscs)mentioning
confidence: 94%
“…Figure 23A shows cross-sectional scanning electron microscope image of a perovskite meso-superstructured solar cell. In general, the optimum concentration of spherical metal NPs was found to be 0.8-0.9 wt% [117,120]. Interestingly, Zhang et al found that photo current enhancement in their developed plasmon-enhanced PSCs arose from the reduction of exciton binding energy with the integration of core@shell Au@SiO 2 NPs into an alumina scaffold [117].…”
Section: Perovskite Solar Cells (Pscs)mentioning
confidence: 99%
See 3 more Smart Citations